Prácticas de enseñanza de lógica matemática en educación inicial del Centro Educativo Marqués de La Fayette - Cevallos Cubero, Cristina Alexandra (2016)
Case analysis: teaching practices of mathemathical logic in Initial Education II, it was performed in “Marqués de la Fayette” school located in San Blas, Parish Quito, Pichincha province, in a neighborhood called “Las Orquídeas”. There are middle and low class children in this school, some of the parents are: entrepreneurs, housewives. All the children are mestizos. This school has an Initial II classroom that have 25 children, 15 boys and 10 girls, this classroom is in charge of a children teacher. This research was done because, according to the “Universidad Politécnica Salesiana” Titration Unit located in Quito, documents or references about Initial Education pedagogical practices doesn´t exist. The intention is to understand how the different categories of the curricular structure, modifies, constructs and reconstructs the pedagogical practices in Initial Level. For the same reason it was necessary to do bibliography research about Mathematical Logic in Initial Education, the math learning at the same level according to Piaget and the teaching practices of maths in Initial level. This reason is complemented with field work, through direct observation, data collection by records, teacher interviews, supplies that help to the results analysis, the presentation and finally get the conclusions.